2000
DOI: 10.1063/1.373598
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on the effect of (La0.5Sr0.5)MnO3 and (La0.5Sr0.5)CoO3 buffer layers on fatigue properties of (Pb0.6Sr0.4)TiO3 thin films prepared by pulsed laser deposition

Abstract: Articles you may be interested inEnhanced magnetoelectric effect in La0.67Sr0.33MnO3/PbZr0.52Ti0.48O3 multiferroic nanocomposite films with a SrRuO3 buffer layer Role of dual-laser ablation in controlling the Pb depletion in epitaxial growth of Pb(Zr0.52Ti0.48)O3 thin films with enhanced surface quality and ferroelectric properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…XRD patterns indicate that PCT10 thin films deposited on a platinum-coated silicon substrate and on a LSCO buffer layer possess a polycrystalline nature without preferential orientation and exhibit a single perovskite phase without any impurity phase (see Fig. 2a (2) and (3)) which is consistent with the report by Song et al [23,28] [25].…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…XRD patterns indicate that PCT10 thin films deposited on a platinum-coated silicon substrate and on a LSCO buffer layer possess a polycrystalline nature without preferential orientation and exhibit a single perovskite phase without any impurity phase (see Fig. 2a (2) and (3)) which is consistent with the report by Song et al [23,28] [25].…”
Section: Methodssupporting
confidence: 82%
“…Among these oxide buffer layers, pseudocubic perovskite La 1 À x Sr x CoO 3 thin films have been intensively studied and have shown a strong influence as a buffer layer [22][23][24]. Cheng et al [25] reported the effects of La 0.5 Sr 0.5 CoO 3 (LSCO) and La 0.5 Sr 0.5 MnO 3 (LSMO) buffer layers on the polarization switching of Pb 1 À x Sr x TiO 3 /LSMO/Pt-Si and Pb 1 À x Sr x TiO 3 /LSCO/Pt-Si thin films. To our knowledge, there are few reports regarding PCT thin films on platinum-coated silicon substrates with LSCO buffer layers and their structural, microstructural and ferroelectric properties have not been investigated.…”
Section: Introductionmentioning
confidence: 99%